Fiscal Consolidation in India : The Way Forward - Gupta, Deepa; Bedarkar, Madhura (Indian Journal of Finance, 2016)
The magnitude of fiscal deficit has always been a cause of concern for policy makers in India. The first step towards fiscal consolidation in India began with implementation of the Fiscal Responsibility and Budget Management (FRBM) Act, 2003 and Fiscal Regulatory Legislation (FSL). Further, the Twelfth Finance Commission proposed incentives for State Governments in order to bring in fiscal discipline at the state level. This paper examined the long term profile and impact of high fiscal deficit, consequent debt to GDP ratio, and the need for fiscal consolidation in India. It also presented the reasons behind non- attainment of the fiscal targets set under the FRBM bill. The paper aimed to contribute to the policy debate on fiscal consolidation in India.